Towards the elaboration of new gold-based optical theranostics. Issue 11 (10th December 2014) - Doulain, Pierre-Emmanuel; Decréau, Richard; Racoeur, Cindy; Goncalves, Victor; Dubrez, Laurence; Bettaieb, Ali; Le Gendre, Pierre; Denat, Franck; Paul, Catherine; Goze, Christine; Bodio, Ewen
Abstract : Four new red BODIPY–gold(i ) theranostic compounds were synthesized. Abstract : Four new red BODIPY–gold(i ) theranostic compounds were synthesized. Some of them were vectorized by tethering a biovector (glucose or bombesin derivatives) to the metallic center. Their photophysical properties were studied. Additionally, their cytotoxicity was examined on different cancer cell lines and on a normal cell line, they were tracked in vitro by fluorescence detection, and their uptake was evaluated by ICP-MS measurements.